2020
DOI: 10.1108/k-03-2020-0124
|View full text |Cite
|
Sign up to set email alerts
|

Investment behaviour in mutual funds: is it a knowledge-based decision?

Abstract: Purpose This paper aims to make an analysis of investment behaviour in mutual funds, by looking at different investment decision influencers and trying to identify the extent to which the investment decision is knowledge-based. The paper has three main purposes, namely, to assess the degree to which the considered factors influence investment decision-making in young capital markets from Central and Eastern Europe (CEE); to compare the investment behaviour in the three considered countries; and to characterise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
3
1
Order By: Relevance
“…Information related to mutual funds is still limited, thus it has not reached all investors in various regions. These results do not in line with the results of Sabri and Afiqah (2016), Ahmad andShah (2022), Hassan Al-Tamimi andAnood Bin Kalli (2009), Jariwala (2015a), Lusardi (2019), and Nicolescu and Tudorache (2021) who found that financial literacy had a positive effect on investment decisions.…”
Section: Hypotheses Testing Resultscontrasting
confidence: 60%
See 2 more Smart Citations
“…Information related to mutual funds is still limited, thus it has not reached all investors in various regions. These results do not in line with the results of Sabri and Afiqah (2016), Ahmad andShah (2022), Hassan Al-Tamimi andAnood Bin Kalli (2009), Jariwala (2015a), Lusardi (2019), and Nicolescu and Tudorache (2021) who found that financial literacy had a positive effect on investment decisions.…”
Section: Hypotheses Testing Resultscontrasting
confidence: 60%
“…Of the 183 investors who invest in PSX, the results show that financial literacy can improve investment decisions. In the Capital Markets of Central and Eastern Europe (CEE), Nicolescu & Tudorache (2021) researched investment behaviour in mutual funds by looking at the effect of financial knowledge and skill analysis on investment decisions. The results show that the investment decisions of investors in the CEE capital market are influenced by knowledge because investors in these regions only consider some of the available information to make investment decisions.…”
Section: Financial Literacy and Investment Decision In Mutual Fundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Today's standard finance is unable to explain the market due to its variation between theory and evidence (Statman, 2018). The investment decision is the blend of knowledge, available information, and behavior of the individual investors (Nicolescu & Tudorache, 2020). The new thought of financial markets emerges, incorporating the inclusion of human emotions, behaviors, and sentiments while making investment decisions (Zahera & Bansal, 2018).…”
Section: Introductionmentioning
confidence: 99%